Analysis of the proficiency of single radial immunodiffusion assays for quality control of influenza vaccines in Korea. (November 2017) - Choi, Yejin; Lee, Sunmi; Kwon, Seong Yi; Lee, Younghee; Park, Yong Keun; Ban, Sang Ja
Abstract: Influenza vaccine potency, which is determined by quantitatively measuring the content of Hemagglutinin (HA), is an essential index representing the efficacy of the vaccine. Standardization of the single radial immunodiffusion (SRID) assay, a method for measuring HA content, and proficiency of the testing institutions are crucial for influenza vaccine quality control. Herein, we assessed the proficiency of SRID assays at the National Control Laboratory (NCL) of Korea and several vaccine manufacturers. Eight laboratories participated in this study, and the proficiencies of all laboratories yielded satisfactory results in overall SRID assays. In contrast, there were some unsatisfactory results in measuring with different types of agarose gel plates produced by other laboratories. Overall, our findings demonstrated that the proficiency of SRID assay in the tested laboratories is acceptable for quality control of influenza vaccines and that detailed review on the validation reports regarding the test methods will be helpful for better control.